Peran BAZNAS Kabupaten Bandung Barat dalam Menyalurkan Zakat Produktif untuk Pengembangan Usaha Pada Semester I Tahun 2025 - Devika Amanda Dahlia Putri; N Dian Anggraeni Nurhalisa; Yulianti Yulianti; Triana Apriani (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
This study aims to comprehensively examine the role of BAZNAS (National Amil Zakat Agency) of West Bandung Regency in the distribution of productive zakat as a means to foster community-based business development during the first semester of 2025. Productive zakat, unlike consumptive assistance, is positioned as a strategic instrument to improve the economic independence of mustahik (zakat recipients), particularly micro-entrepreneurs such as small shop owners, farmer groups, tailors, and individuals engaged in similar economic activities. The research adopts a descriptive qualitative approach to capture an in-depth understanding of program implementation. Data collection methods include in-depth interviews with BAZNAS officials, serving as key informants, and the examination of relevant documents, reports, and activity records. The findings indicate that the application process for assistance is conducted through formal, verified requests, ensuring transparency and accountability, rather than accepting open-form submissions. The form and amount of assistance are adjusted to the specific type and needs of each business, and recipients are prioritized based on the eight asnaf categories, with a focus on those who already have ongoing business activities. In addition to capital provision, the program aims to empower mustahik to transition into muzakki (zakat givers) over time, thereby creating a sustainable cycle of economic empowerment. Monitoring activities are conducted three times a year to assess progress and identify challenges. However, the study also highlights constraints, including limited mentoring sessions and the need for more consistent supervision to ensure that the assistance translates into long-term economic impact. To maximize effectiveness, stronger collaboration among BAZNAS, local communities, and regional government is recommended, alongside capacity-building initiatives for beneficiaries. This collaborative approach is expected to reinforce the sustainability and impact of productive zakat programs, contributing to broader poverty reduction and community empowerment goals.